Patterns, determinants and models of woody plant diversity in China - Wang, Zhiheng; Fang, Jingyun; Tang, Zhiyao; Xin Lin (Proceedings of the Royal Society B: Biological SciencesProceedings of the Royal Society B: Biological Sciences, 2011)
What determines large-scale patterns of species richness remains one of the most controversial issues in ecology. Using the distribution maps of 11 405 woody species in China, we compared the effects of habitat heterogeneity, human activities and different aspects of climate, particularly environmental energy, water–energy dynamics and winter frost, and explored how biogeographic affinities (tropical versus temperate) influence richness–climate relationships. We found that the species richness of trees, shrubs, lianas and all woody plants strongly correlated with each other, and more strongly correlated with the species richness of tropical affinity than with that of temperate affinity. The mean temperature of the coldest quarter was the strongest predictor of species richness, and its explanatory power for species richness was significantly higher for tropical affinity than for temperate affinity. These results suggest that the patterns of woody species richness mainly result from the increasing intensity of frost filtering for tropical species from the equator/lowlands towards the poles/highlands, and hence support the freezing-tolerance hypothesis. A model based on these results was developed, which explained 76–85% of species richness variation in China, and reasonably predicted the species richness of woody plants in North America and the Northern Hemisphere.